Algebra, geometry, and software systems - Joswig Michael; Takayama Nobuki (Berlin Springer-Verlag, 2003)
A collection of surveys and research papers on mathematical software and algorithms. The common thread is that the field of mathematical applications lies on the border between algebra and geometry. Topics include polyhedral geometry, elimination theory
Keywords: Computer mathematics; Mathematical software